PROJECT MANAGEMENT PERFORMANCE ANALYSIS FOR IMPROVING ROAD CONSTRUCTION IMPLEMENTATION KARAWANG CIKAMPEK PAMANUKAN - Tiki Rysianne; Abdul Chalid (RADJA PUBLIKA, 2026)
This study aims to determine and analyze the influence of planning, organizing, implementing, and supervising the performance of the Karawang-Cikampek-Pamanukan road construction project , both partially and simultaneously . The research method used in this study is a quantitative research method. This study was conducted on the Karawang-Cikampek-Pamanukan road construction improvement project by collecting data using a questionnaire , the sample used was 45 respondents. The data source in this study is primary data with multiple linear regression analysis and hypothesis testing, with data processing using SPSS software version 26. The results of the study indicate that planning has a positive and significant effect on the performance of the Karawang-Cikampek-Pamanukan road construction improvement project . Organizing has a positive and significant effect on the performance of the Karawang-Cikampek-Pamanukan road construction improvement project . Implementation has a positive and significant effect on the performance of the Karawang-Cikampek-Pamanukan road construction improvement project . Supervision has a positive and significant effect on the performance of the Karawang-Cikampek-Pamanukan road construction improvement project . Project management consisting of planning, organizing, implementing, and supervising has a significant influence on the performance of the Karawang–Cikampek–Pamanukan Road construction improvement project .